A refractory liver metastatic solid pseudopapillary neoplasm pancreas harbored CTNNB1 mutation showed good response to celecoxib: A case report - Shang, Yu; Zhang, Yunkun; Pan, Evenki; Yang, Peng; Xu, Lingling; Sun, Jinghua (Frontiers in Oncology, 2022)
Solid pseudopapillary neoplasm (SPN) of the pancreas is rare relatively low-grade malignant neoplasm and metastasis rarely. Surgical resection is the primary treatment option for primary and metastatic lesions of SPN, and chemotherapy is often ineffective in non-operable SPNs. SPNs are characterized by the presence of somatic CTNNB1 exon 3 mutations, leading to the activation of Wnt/β-catenin/Cox-2 signal pathway. Here, we firstly report that a refractory liver metastatic pancreatic SPN patient after the failure of multi-line chemotherapies benefited from the Cox-2 selective inhibitor (Celecoxib) based on CTNNB1 D32V mutation detected by next-generation sequencing (NGS), achieving a more than 22-month progression-free survival without any adverse events. Our case provides a potential treatment option for liver metastatic SPN patients with CTNNB1 mutations and highlights the application of NGS for the better treatment decision making.